2023
DOI: 10.1101/2023.08.31.555785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tick hemocytes have pleiotropic roles in microbial infection and arthropod fitness

Agustin Rolandelli,
Hanna J. Laukaitis-Yousey,
Haikel N. Bogale
et al.

Abstract: Uncovering the complexity of systems in non-model organisms is critical for understanding arthropod immunology. Prior efforts have mostly focused on Dipteran insects, which only account for a subset of existing arthropod species in nature. Here, we describe immune cells or hemocytes from the clinically relevant tickIxodes scapularisusing bulk and single cell RNA sequencing combined with depletion via clodronate liposomes, RNA interference, Clustered Regularly Interspaced Short Palindromic Repeats activation (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Hemocytin is differentially expressed in R. parkeri- infected A. maculatum hemocytes ( 9 ). A recent study also showed an increased Anaplasma phagocytophilum load in hemocytin-silenced tick ( 23 ), further supporting our observation. These results support that hemocytin is an essential component of the tick cellular immune response and is required for regulating intracellular pathogen infection within the tick vector.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hemocytin is differentially expressed in R. parkeri- infected A. maculatum hemocytes ( 9 ). A recent study also showed an increased Anaplasma phagocytophilum load in hemocytin-silenced tick ( 23 ), further supporting our observation. These results support that hemocytin is an essential component of the tick cellular immune response and is required for regulating intracellular pathogen infection within the tick vector.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, these techniques often fail to capture the full spectrum of cellular diversity and functional heterogeneity at the single-cell level, limiting our understanding of the intricate cellular immune responses accompany blood feeding or infection. Single-cell RNA sequencing (scRNA-seq) has redefined our understanding of hemocyte populations in invertebrate models such as Drosophila ( 15 17 ), mosquito ( 18 20 ), silkworm and moth ( 21 , 22 ), ticks ( 23 ) and aquatic invertebrates ( 24 26 ). Applying scRNA-seq in these organisms has led to identifying additional hemocyte complexity and cell types when compared to previous classifications ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional studies of tick hemocytes (Kotsyfakis et al, 2015; Adegoke et al, 2023) have revealed important information regarding the molecular regulation of tick hemocytes during physiological processes such as blood feeding or microbial infection. Nevertheless, these techniques often fail to capture the full spectrum of cellular diversity and functional heterogeneity at the single-cell level, limiting our understanding of the intricate cellular immune responses accompany blood feeding or infection.. Single-cell RNA sequencing (scRNA-seq) has redefined our understanding of hemocyte populations in invertebrate models such as Drosophila (Cattenoz et al, 2020; Cho et al, 2020; Tattikota et al, 2020), mosquito (Severo et al, 2018; Raddi et al, 2020; Kwon et al, 2021), silkworm and moth (Feng et al, 2021; Feng et al, 2022), ticks (Rolandelli et al, 2023) and aquatic invertebrates (Koiwai et al, 2021; Pichon et al, 2022; Cui et al, 2022). Applying scRNA-seq in these organisms has led to identifying additional hemocyte complexity and cell types when compared to previous classifications (Raddi et al, 2020; Kwon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%